Efektivitas Strategi Pembelajaran Group To Group Exchange Pada Materi Himpinan Di Mts Nurul Ihsan - Mutmainnah, Mutmainnah (APOTEMA : Jurnal Program Studi Pendidikan Matematika, 2017)
Based on this research are the less effective students and teachers during the learning process because the center of teaching is the teacher itself. Students are less active in learning so that students responses become passive and students learning outcomes are not complete. One way to solve these problems by applied the strategy of learning group to group exchange. This study was conducted with the aim of: (1) to describe the ability of teachers to manage learning using group-to-group exchange strategy (2) to describe the student activity in learning using group-to-group exchange strategy (3) to describe the students response to learning using the strategy Group to group exchange (4) to describe the result of students learning after being taught using group to group exchange strategy. This research used descriptive quantitative research. The method is used observation, questionnaires and tests.The result of analysis data statistic descriptive show that, the teachers can manage Group to Group Exchange Learning which the result 3,71 in best category. Student activities during active lessons. This is indicated by an average of 3,03 which is included in the active category. Student response after learning is said to be positive, because the average percentage of positive responses across students reaches 95%. Studentsâ learning completeness in the classical achieved because the percentage of the number of student reached 83%.   Keywords : Effectiveness, Learning strategy Group to Group Exchange.